Comparative Evaluation of Dexmedetomidine-Midazolam and Fentanyl-Midazolam for Sedation and Analgesia in Lower Extremity Orthopedic Surgery under Spinal Anesthesia: A Randomized Double-Blind Clinical Trial - Mojgan Rahimi; Mohamad Sorani; Afzal Shamsi; Myasar Jasim Mohamad; Noah Awad Hussain (Archives of Anesthesia and Critical Care, 2026)
Background: Spinal anesthesia is a very commonly used procedure in modern-day anesthesia practice. Today most of the lower limb surgeries are performed under spinal anesthesia. Midazolam, dexmedetomidine, and fentanyl are common intravenous adjuvants used during anesthesia to allay anxiety and sedation. The aim of this study was to compare the effects of intravenous dexmedetomidine-midazolam versus fentanyl-midazolam in terms of analgesic characteristics, sedation, and adverse effects. Methods: This is a randomized prospective study that included 35 patients in each group, posted for lower limb orthopedic surgery. Intravenous dexmedetomidine, fentanyl, and midazolam were administered after subarachnoid block. Data for sedation, analgesia, hemodynamic parameters, and adverse effects were recorded. Results: RR for FM group showed significant intra-group variability in RR across perioperative stages (p